Nutrient supply and accessibility in plants: effect of protein and carbohydrates on Australian plague locust (Chortoicetes terminifera) preference and performance - Brosemann, Jonah; Overson, Rick; Cease, Arianne J.; Millerwise, Sydney; Le Gall, Marion (Frontiers in Insect Science, 2023)
In contrast to predictions from nitrogen limitation theory, recent studies have shown that herbivorous migratory insects tend to be carbohydrate (not protein) limited, likely due to increased energy demands, leading them to preferentially feed on high carbohydrate plants. However, additional factors such as mechanical and chemical defenses can also influence host plant choice and nutrient accessibility. In this study, we investigated the effects of plant protein and carbohydrate availability on plant selection and performance for a migratory generalist herbivore, the Australian plague locust, Chortoicetes terminifera. We manipulated the protein and carbohydrate content of seedling wheat (Triticum aestivum L.) by increasing the protein:carbohydrate ratio using nitrogen (N) fertilizer, and manipulated the physical structure of the plants by grinding and breaking down cell walls after drying the plants. Using a full factorial design, we ran both choice and no-choice experiments to measure preference and performance. We confirmed locust preference for plants with a lower protein-carbohydrate ratio (unfertilized plants). Unlike previous studies with mature wild grass species, we found that intact plants supported better performance than dried and ground plants, suggesting that cell wall removal may only improve performance for tougher or more carbohydrate-rich plants. These results add to the growing body of evidence suggesting that several migratory herbivorous species perform better on plants with a lower protein:carbohydrate ratio.